Influence of Human Behavior on Success of Complex Public Infrastructural Megaprojects in Kenya - Austin Baraza Omonyo (European Scientific Journal, ESJ, 2017)
The main objective of this study was to investigate the influence of human behavior on the success of public infrastructural megaprojects in Kenya. The need for this study arose from the thesis that complexity due to human behavior is the main cause of waste and failure that results in infrastructural megaprojects being delivered over budget, behind schedule, with benefit shortfalls, over and over again. The study was designed as multiple-method research, based on virtual constructionist ontology recognizing that complexity is the mid-point between order and disorder. A cross-sectional census survey of 27 completed public infrastructural megaprojects was conducted using two interlinked questionnaires assessing human behavior constructs and project success. A total of 108 respondents made up of project managers, team members and organizational sponsors, participated in this study. Using both descriptive and inferential analysis, the results of this study have confirmed that human behavior significantly influences success of public infrastructural megaprojects. Optimism bias remains the main individual behavior that leads to cost and schedule underperformance in infrastructural megaprojects but loss aversion is the most occurring cognitive bias. In light of this finding, the study recommends that implementing organizations adopt structures that allow for continued business justification, focus on products and give project managers sufficient authority over project resources in line with the postulations of the structural contingency theory.